Synthetic cannabinoid "Black Mamba" infidelity in patients presenting for emergency stabilization in Colorado: a P SCAN Cohort. (4th March 2018) - Brandehoff, Nicklaus; Adams, Axel; McDaniel, Kyle; Banister, Samuel D.; Gerona, Roy; Monte, Andrew A.
Abstract: Background: Use of new psychoactive substances (NPS) has increased over the last decade. During this period, variability of both clinical presentations and chemical compositions of these compounds has increased. Synthetic cannabinoids (SCs) are the most commonly used NPS and there are more than 100 documented unique molecules in this class. "Black Mamba", often associated to ADB-FUBINACA, is the most commonly used SC in Colorado. It has been linked to kidney injury, myocardial toxicity, seizures, and death. Objectives: We aim to identify the chemical constituents and quantification of eight cases of reported "Black Mamba" use in order to further understand the clinical variability in patients presenting for emergency stabilization. Methods: We report data from eight cases of reported "Black Mamba" use prospectively captured through the Colorado site of the Psychoactive Surveilance Consortium and Analysis Network (P SCAN). P SCAN is a geographically representative group of academic hospitals that capture clinical presentation, outcome, and biologic samples from patients that present for emergency stabilization following NPS use. Serum and urine samples were analyzed and quantified by liquid chromatography-quadrupole time-of-flight mass spectrometry after a qualitative screen for over 600 unique NPS compounds. Results: In the reported eight cases, the median age was 28 years old. There were four male and four females. Four patients had agitation/delirium and four patients had chest pain. Normal saline, benzodiazepines and ondansetron were the common treatment provided in the emergency department (ED). Two patients were discharged from the ED and six patients being admitted for emergency observation with a median length of stay (LOS) of six hours. No deaths were reported. Confirmatory testing revealed that only five patients (62.5%) had SCs found in blood or urine samples. Cocaine, NRG-3, 3-methoxyphencyclidine hydrochloride (MeO-PCP), and methamfetamine were identified in other presentations. Conclusions: The wide range of clinical presentations from "Black Mamba" use may be explained by the wide variability of chemical constituents found by laboratory analysis.